1997
DOI: 10.1042/bj3270735
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of Na+-dependent phosphate co-transporters to phosphate transport in mouse kidney: RNase H-mediated hybrid depletion analysis

Abstract: Reabsorption of Pi in the proximal tubule of the kidney is an important determinant of Pi homoeostasis. At least three types (types I-III) of high-affinity Na+-dependent Pi co-transporters have been identified in mammalian kidneys. The relative roles of these three types of Na+/Pi co-transporters in Pi transport in mouse kidney cortex have now been investigated by RNase H-mediated hybrid depletion. Whereas isolated brush-border membrane vesicles showed the presence of two kinetically distinct Na+/Pi co-transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In this study, we used an antisense hybrid depletion approach in Xenopus laevis oocytes to investigate the functional significance of PMAT in the brain. This method has been widely used to evaluate the relative importance of a specific transporter to total tissue uptake [16][17][18][19][20]. Because our data suggested a significant role of PMAT in total brain 5-HT uptake, potential pharmacological interactions between the SSRIs and PMAT have also been investigated.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this study, we used an antisense hybrid depletion approach in Xenopus laevis oocytes to investigate the functional significance of PMAT in the brain. This method has been widely used to evaluate the relative importance of a specific transporter to total tissue uptake [16][17][18][19][20]. Because our data suggested a significant role of PMAT in total brain 5-HT uptake, potential pharmacological interactions between the SSRIs and PMAT have also been investigated.…”
Section: Introductionmentioning
confidence: 84%
“…Previously, the hybrid depletion approach has been used to estimate the relative contribution of a number of individual membrane transporters to tissue-specific uptake of a ligand [16][17][18][19][20]. This relatively simple and straightforward method allows evaluation of gene function in human tissues that can not be easily studied in genetic knockout models.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were anesthetized with Nembutal (50 mg/kg of body weight, intraperitoneally) and killed by aortic puncture. Total RNA was isolated from rat kidney cortex by acid guanidine thiocyanate/phenol/chloroform extraction (12). Total RNA samples were separated by electrophoresis on 1.2% agarose gels containing 2.2 M formaldehyde and transferred to Hybond-N membranes (Amersham, Buckinghamshire, United Kingdom) and covalently cross-linked by exposure to UV light.…”
Section: Methodsmentioning
confidence: 99%
“…The antibodies were raised against a peptide that represented an amino acid sequence (Leu-Ala-Leu-Pro-Ala-HisHis-Asn-Ala-Thr-Arg-Leu, amino acids 626 -637) in the C-terminal region of NaPi-2 or an amino acid sequence (Met-Met-Ser-Tyr-Ser-GluArg-Leu-Gly-Gly Pro-Ala-Val-Ser, amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] in the N-terminal region of NaPi-2 (3). An N-terminal cysteine residue was introduced for conjugation with keyhole limpet hemocyanine (Sigma) using m-maleimidobenzoyl-N-hydroxysuccinimide ester.…”
Section: Identification Of Three Napi-2 Related Proteinsmentioning
confidence: 99%
“…6-s In addition, RNAse-H mediated hybrid-depletion analysis has shown that the type II Na § cotransporer mediated most Na+-dependent Pi transport in the kidney cortex of mice. 9 Furthermore, a strong candidate gene for Xlinked hypophosphatemia was reported. 1~ Pex (a phosphate-regulating gene with homologies to endopeptidases on the X-chromosome) appears to be the site of the molecular defect that causes X-linked hypophosphatemia.…”
mentioning
confidence: 99%